CALCULATE GRAIN SIZE DISTRIBUTION AND MECHANISM OBSERVATION OF WELL SANDING INDUCED BY LOMBOKâS EARTHQUAKE - Isnaini Romli, Nur
Sand production or sanding is a phenomenon where sand grains are released from reservoir formations around boreholes or perforations. The loose sand grains have a hydrodynamic force when producing hydrocarbons so they are carried along with the fluid. Sand production causes serious problems in the petroleum industry. Sanding can also occur due to vibrations on the earth or earthquakes that cause changes in the vertical direction vector pressure on the ground, the phenomenon is usually called liquefaction. Factors causing sanding are reservoir formation that is not well consolidated, rock mechanics such as overburden or inter-grain friction, reservoir lithology formations such as cementation of the material or particle size, fluid characteristics such as viscosity, production rate which affects drawdown pressure, increased water production. In this study, we used well samples at 7 locations affected by the earthquake. From the seven samples measured grain size distribution and simulation of vertical stress vector values on the soil to a depth of 20000 meters during an earthquake to find out depth the ground was experiencing liquefaction. The results obtained that when the earthquake occurred in the sample 1,3,5,6 will undergo liquefaction to a depth of 4700 meters, 13400 meters, 8700 meters, 5600 meters. While for the 2,4,7 sample at a depth of 20000 meters, it still undergo liquefaction